The Influence of Social Media Influencer Utilization in Influencing Public Opinion - Loso Judijanto; Sitti Harlina; Muhammad Yusuf; Ni Desak Made Santi Diwyarthi; Bekti Setiadi (West Science Social and Humanities Studies, 2024)
This bibliometric analysis delves into the evolving landscape of research surrounding the impact of social media influencers on public opinion. Spanning nearly six decades and comprising 980 scholarly publications, the study employs rigorous bibliometric tools to unveil clusters of research themes, influential authors, and emerging trends. The analysis reveals the multifaceted role of social media influencers, spanning domains from consumer behavior to political discourse. Implications drawn from the findings highlight growing interdisciplinary interest and suggest potential avenues for future research, while the density visualization underscores well-explored and less-explored dimensions within the literature. As the influence of social media influencers continues to evolve, this study serves as a comprehensive guide, informing policymakers, marketers, and scholars about the complex interplay between digital influencers and societal perceptions.